التطوع فى المکتبات الأکادیمیة لتلبیة احتیاجات سوق العمل - د. سفانة عبد القادر زیدان (المجلة الدولية لعلوم المكتبات والمعلومات)
Employment skills can't be effectively developed in the classroom, butvolunteer-based training and experience have had an effective impact on instillingemployment skills in graduates, increasing their career prospects, and learninghow to organize their academic and social life more effectively. As a result of thevolunteer mixing the learning experiences and practical experience resulting fromthe volunteer tasks in the library, which contributes to the acquisition of manynecessary skills needed for learning and work. In this context, this research aims tostudy the volunteer program in the academic libraries and its importance inproviding the volunteers with the necessary skills to meet the needs of workrequirements ,and how they can be used to fill the gap in professionals inacademic libraries in order to meet the library's need to provide effective serviceson and off campus.The researcher used the descriptive analysis method to study thevolunteer program in the academic library at Imam Abdul Rahman bin FaisalUniversity describing qualitatively and quantitatively. The research communityconsisted of the volunteers in the academic library - And it was carried out in theacademic year 2017/2018. The total number (34) volunteers, who responded tothe search instrument correctly, of (54) volunteers; Up 63% of the total number ofvolunteers this year.The results of the study revealed that the highest experience and skillsgained during the participation in the library volunteering program were: (Skills ofsearching for information sources, communication and customer service skills,teamwork skills, social skills and human relations skills) which needed for work.This study can be considered as a guide to explain the role of academic libraries in inproviding volunteers with the practical, scientific and life skills required to meetthe needs of the work. As well as benefiting from them in filling the gap ofprofessionals to improve the services of the academic library in the university. Finally   the researcher concluded with a set of recommendations and suggestions based on theresults of the research.